Ultrafast densification of high-entropy oxide (La0.2Nd0.2Sm0.2Eu0.2Gd0.2)2Zr2O7 by reactive flash sintering. Issue 4 (April 2021) - Mao, Hai-Rong; Guo, Rui-Fen; Cao, Yue; Jin, Shen-Bao; Qiu, Xiao-Ming; Shen, Ping
Graphical abstract: Highlights: Nearly fully dense HEPOs were prepared by RFS at a low furnace temperature in seconds. The RFSed-HEPOs displayed compositional uniformity at the atomic level. The roles of electric field, rapid heating and external pressure during RFS were discussed. The RFSed-HEPOs exhibited superior modulus, hardness and fracture toughness. Abstract: Pyrochlore-type high-entropy oxides (HEOs) are usually sintered at high temperatures for a long time to achieve full density. Herein, we synthesized pyrochlore-structured (La0.2 Nd0.2 Sm0.2 Eu0.2 Gd0.2 )2 Zr2 O7 HEOs with densities up to 99 % at a furnace temperature of 1200 °C in seconds via reactive flash sintering (RFS). The resultant HEOs achieved compositional uniformity at the atomic level and exhibited superior modulus, hardness and fracture toughness compared to the counterparts prepared by conventional solid-state sintering (at 1600 °C for 6 h). The underlying mechanisms for the ultrafast densification of the RFSed-HEOs were addressed in view of the roles of electric field, rapid heating, external pressure and internal reactions.